2019
DOI: 10.3389/fmicb.2018.03201
|View full text |Cite
|
Sign up to set email alerts
|

Early Response of Sulfolobus acidocaldarius to Nutrient Limitation

Abstract: In natural environments microorganisms encounter extreme changes in temperature, pH, osmolarities and nutrient availability. The stress response of many bacterial species has been described in detail, however, knowledge in Archaea is limited. Here, we describe the cellular response triggered by nutrient limitation in the thermoacidophilic crenarchaeon Sulfolobus acidocaldarius. We measured changes in gene transcription and protein abundance upon nutrient depletion up to 4 h after initiation of nutrient depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 92 publications
6
35
0
Order By: Relevance
“…Zhou et al conducted continuous cultivations and regulated the growth rate via the feed addition while a constant temperature, pH and aeration rate was given [78]. Slower growth rates increased the cyclization, which is in conformity with the experiments conducted with the nutrient depleted medium by Bischof et al [79] The RI changed from 2.0 in the highest applied growth rate of µ = 0.069 h −1 to 3.2 when a slow growth of µ = 0.01 h −1 was set. The amount of GDGT-4 to 6 increased with the decreasing growth rate.…”
Section: Growth Ratesupporting
confidence: 58%
See 3 more Smart Citations
“…Zhou et al conducted continuous cultivations and regulated the growth rate via the feed addition while a constant temperature, pH and aeration rate was given [78]. Slower growth rates increased the cyclization, which is in conformity with the experiments conducted with the nutrient depleted medium by Bischof et al [79] The RI changed from 2.0 in the highest applied growth rate of µ = 0.069 h −1 to 3.2 when a slow growth of µ = 0.01 h −1 was set. The amount of GDGT-4 to 6 increased with the decreasing growth rate.…”
Section: Growth Ratesupporting
confidence: 58%
“…Harvesting and subsequent transfer into nutrient rich and depleted medium was performed at an OD 600 of 0.4 to 0.5, which might suggest that, at this time point, the cells were still in the exponential phase and the previously described drop in average cyclization still took place. A slight decrease in the DEL amount upon nutrient depletion was observed, as shown in their Supplementary Material [79].…”
Section: Growth Ratementioning
confidence: 66%
See 2 more Smart Citations
“…A third factor with supposedly high potential to impact the lipid composition is (3) the level of energy and nutrient supply of the culture. A study performed by Bischof et al (2019) showed that complete starvation of the uracil auxotrophic strain S. acidocaldarius MW001 resulted in a higher number of cyclopentane rings compared to nutrient rich conditions.…”
mentioning
confidence: 99%